The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15288/jsad.2015.76.21
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alcohol Policies in Preventing Intimate Partner Violence: A Review of the Literature

Abstract: Objective-This article summarizes existing research on the relationship between alcohol policies and intimate partner violence (IPV). Because alcohol represents an important risk factor for IPV, interventions and policies aimed at decreasing problem drinking may also lead to reductions in IPV.Method-Electronic databases were searched to identify relevant peer-reviewed journal articles on alcohol policies and IPV, as well as reference sections of appropriate articles. Only policies that have been studied specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 74 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Two reviews focused on intimate partner violence (IPV) (Kearns, Reidy, & Valle, 2015;Wilson, Graham, & Taft, 2014) came to somewhat divergent conclusions. Wilson et al (2014) focused on the period between January 1992 and March 2013.…”
Section: Studies Examining Both Alcohol Prices and Alcohol Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two reviews focused on intimate partner violence (IPV) (Kearns, Reidy, & Valle, 2015;Wilson, Graham, & Taft, 2014) came to somewhat divergent conclusions. Wilson et al (2014) focused on the period between January 1992 and March 2013.…”
Section: Studies Examining Both Alcohol Prices and Alcohol Availabilitymentioning
confidence: 99%
“…For studies on pricing, hours of sale, and outlet density there was weak evidence of impact on IPV. Kearns et al (2015) examined 18 studies published between 1998 and 2013. They concluded that most studies of higher alcohol outlet density showed an association with higher IPV.…”
Section: Studies Examining Both Alcohol Prices and Alcohol Availabilitymentioning
confidence: 99%
“…Accordingly, addressing problematic alcohol use is recognised by WHO as a way to reduce IPV [3]. However, recent reviews found only weak evidence of the effectiveness of alcohol policies and interventions on IPV, with few studies of good quality to provide meaningful conclusions [6,7]. These reviews highlighted the need to know more about the dynamics of how alcohol contributes to violence, in order to design effective approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol-impaired driving—driving after consuming a sufficient amount of alcohol to potentially affect driver performance—is a major cause of accidents (Room, Babor, & Rehm, 2005; Kearns, Reidy, & Valle, 2015; Williams, 2006). Major depression is a prevalent psychiatric disorder among persons who drive while impaired (DWI), and many of its symptoms are associated with DWI(Freeman, Maxwell, & Davey, 2011; Laphamet al, 2001; Lapham, Baca, McMillan, & Lapidus, 2006; Stoduto et al, 2008; Conner, Pinquart, & Gamble, 2009; Sarsour et al, 2012).…”
Section: Introductionmentioning
confidence: 99%